Evaluation of nutritional profile of pulses consumed in Pakistan - Soomro, Hafeezullah; Soomro, Aijaz Hussain; Haider, Muhammad Samee; Tarar, Omer Mukhtar (Journal of Pure and Applied Agriculture, 2023)
Pulses are the world's most beneficial nourishment because of its nutritious profile. Protein quality in pulses is clearly impacted due to their chemical structure. In this study, the diverse pulses i.e. chickpea white, chickpea dark-colored, split chickpea, red lentil, yellow lentil, white lentil, red kidney bean and a black eye or goat bean were collected from the different regions of the country for comparative composition of fat solvent vitamins (A, E and β-carotene) and amino acids. The results demonstrated that pulses contained high protein contents from 18 to 24%, dietary fibre from 2 to 4%, lipids from 0.7 to 5%, dietary fiber 10.86 to 26.03%, while starch